Inferring the biogeography of New Zealand's only endemic holoparasitic plant, the threatened Dactylanthus taylorii (Mystropetalaceae). Issue 4 (2nd October 2022) - McLay, Todd G. B.; Tate, Jennifer A.; Gemmill, Chrissen E. C.; Holzapfel, Avi S.; Symonds, V. Vaughan
ABSTRACT: Despite a rich history of botanical research, little is known about the distribution of genetic variation within New Zealand plant species. With a native vascular flora that consists of ∼80% endemics, nearly one-half of which are threatened, there is a dire need for a better understanding of intraspecific diversity for individual plant species and of biogeographic patterns for the wider New Zealand flora. To these ends, we have investigated population genetic structure in the endemic root holoparasite, Dactylanthus taylorii (pua o te Rēinga, Mystropetalaceae). A total of 235 individuals from 31 locations across the North Island of New Zealand (Te Ika-a-Māui, Aotearoa) were genotyped for a suite of nuclear microsatellite loci. Genotype data were analysed at the individual and population levels to assess genetic diversity within and among populations and to investigate the geographic distribution of genetic variation within the species. Population structure was assessed using Bayesian clustering, discriminant analysis of principal components, and a Neighbor-Net analysis. A hierarchical pattern of genetic diversity was revealed, with evidence for three broad geographic regional groupings (West, East, and Central Volcanic Plateau (CVP)). Upon further analysis, each of the three geographic groups further subdivide hierarchically into two or three genetic subgroups. Genetic diversity was found to be relatively high in this endangered species but varies considerably across populations. The distribution of genetic groups appears to have been influenced by past volcanic activity as the CVP group is largely coincident with a distinct tephra isopach from the 1.8 ka Taupō eruption and the West and East groups may have diverged due to recurring volcanic activity in the Central Volcanic Zone. The genetic structure resolved here provides important information for the management of D. taylorii specifically and for our understanding of New Zealand biogeography generally.